A machine learning approach to analysis and classification of measurements in cultural heritage - Sevetlidis, Vasileios; Σεβετλίδης, Βασίλειος (2020)
Treatment of spectral information is an essential tool for the examination of various cultural heritage materials. Raman Spectroscopy has become an everyday practice for compound identification due to its non-intrusive nature, but often it can be a complex operation. Spectral identification and analysis on artists' materials is being done with the aid of already existing spectral databases and spectrum matching algorithms. We demonstrate that with a machine learning method called Extremely Randomised Trees, we can learn a model in a supervised learning fashion, able to accurately match an entire-spectrum range into its respective mineral. Our approach was tested and was found to outperform the state-of-the-art methods on the corrected RRUFF dataset, while maintaining low computational complexity and inherently supporting parallelisation.